Pediatric P‐ANCA vasculitis following COVID‐19. Issue 10 (11th August 2021) - Fireizen, Yaron; Shahriary, Cyrus; Imperial, Maria E.; Randhawa, Inderpal; Nianiaris, Nastasia; Ovunc, Bugsu
Abstract: Background: Perinuclear anti‐neutrophil cytoplasmic antibodies (P‐ANCA) are associated with a multisystem vasculitis affecting small blood vessels in the body. A handful of adult patients who developed vasculitis post‐COVID‐19 have been reported. Although SARS‐CoV‐2 has been shown to drive an exaggerated immune response in the pediatric population, such as in Multisystem Inflammatory Syndrome in Children (MIS‐C), only one case of vasculitis following COVID‐19 has been reported previously in children. Case presentation: Seventeen‐year‐old male with a past medical history of COVID‐19 pneumonia two months prior presented with acute kidney injury and diffuse alveolar hemorrhage. Rheumatologic workup revealed P‐ANCA and Myeloperoxidase (MPO) positivity. Kidney biopsy showed necrotizing glomerulonephritis with limited immune complex deposition. Subsequently, he was treated with steroids and plasmapheresis, and ultimately started on cyclophosphamide. Conclusions: To our knowledge, this report presents the second reported pediatric case of P‐ANCA/MPO vasculitis following COVID‐19. Highlights: Autoimmune development postinfectious process. Autoimmune disease and its association to SARS‐CoV‐2 infection. Pediatric P‐ANCA vasculitis post COVID‐19